Australian Survey of Social Attitudes, 2011 - Evans, Ann (ADA Dataverse, 2017)
The 2011 Australian Survey of Social Attitudes (AuSSA) is the fifth in a biennial series that studies social attitudes and behaviour of Australian citizens for the Australian and international research community. AuSSA provides cross-sectional data on the social attitudes and behaviour of Australians, repeating a core questionnaire for each cross-section and fielding specific modules relevant to the changing needs of the social research community. AuSSA is Australia's official survey in the International Social Survey Program (http://www.issp.org) and regularly includes ISSP modules. AuSSA 2011 includes both the ISSP's Environment III (2010) and Health (2011) modules. The 2011 Survey includes attitudes and behaviours that are organised into seven categories: Issues facing Australia today; Environment; Health; Government Policy and services; Kindness; Australians in History; and The Law and Authority. AuSSA 2011 also includes demographic and behavioural categories (Personal Background) that survey: sex, year born, income, education, employment, union membership, country of birth, household composition and religion. There are also questions about the partner of the respondent: employment, highest-level of education and income.